THE EFFECT OF CREDIT RISK, LIQUIDITY RISK, AND OPERATIONAL RISK ON PROFITABILITY (A Study on Conventional Commercial Banks Listed on the Indonesia Stock Exchange) - Ni Kadek Astanggi; I Gde Kajeng Baskara (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Banks are institutions that function as financial intermediaries between parties with excess funds and those with a shortage of funds. The main objective of banks is to generate profit. Banks face various risks due to the involvement of public funds in their operational activities. These risks may lead to losses if not managed properly, and consequently affect the profits earned by the banks. This study aims to determine the effect of Credit Risk, Liquidity Risk, and Operational Risk on Profitability in Conventional Commercial Banks listed on the Indonesia Stock Exchange for the period 2021–2023. The data used is sourced from the financial data in each bank’s annual report and the website www.idx.co.id. The population in this study includes 43 Conventional Commercial Banks. The sampling technique used is purposive sampling, resulting in a sample of 33 banks. The analytical model employed is multiple linear regression analysis with simultaneous testing (F-test) and partial testing (T-test) using IBM SPSS Statistics 25. The results show that Credit Risk, Liquidity Risk, and Operational Risk simultaneously affect Profitability. The partial test results indicate that Credit Risk, Liquidity Risk, and Operational Risk have an influence on Profitability.